1998
DOI: 10.21273/jashs.123.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Diallel Analysis of Resistance to Cuticle Cracking in Tomato

Abstract: Genetic control of cuticle cracking (CC) in tomatoes (Lycopersicon esculentum Mill.) was studied using half-diallel analyses and reciprocal hybrid comparisons of five parents and reciprocal F1 hybrids over 3 years in Bradenton, Fla. Maternal effects were usually not significant, but in general, CC incidence in hybrids with a resistant cultigen as the female parent was lower than if the resistant cultigen was the male parent. General combining ability (GCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Logistic regression analysis indicated that fruit volume had a positive effect on cracking rate in pomegranate. Previous studies on tomato and sweet cherry showed that larger fruits were more sensitive to cracking than small fruits (Emmons and Scott, 1998;Koske et al, 1980;Sekse, 1987;Tucker, 1934). According to Considine and Brown (1981), the force on the containing membrane increases as the radius of the spheroid increases.…”
Section: Fruit Volumementioning
confidence: 95%
See 2 more Smart Citations
“…Logistic regression analysis indicated that fruit volume had a positive effect on cracking rate in pomegranate. Previous studies on tomato and sweet cherry showed that larger fruits were more sensitive to cracking than small fruits (Emmons and Scott, 1998;Koske et al, 1980;Sekse, 1987;Tucker, 1934). According to Considine and Brown (1981), the force on the containing membrane increases as the radius of the spheroid increases.…”
Section: Fruit Volumementioning
confidence: 95%
“…Logistic regression analysis showed that the relationship between skin thickness and the resistance to fruit cracking in pomegranate was not significant. In a study, Emmons and Scott (1998) and Matas et al (2004) found that the cracking-resistant genotype of tomato had a thicker epidermal and cuticle layer than the sensitive genotype. In contrast, Lane et al (2000) suggested the skin's role in cracked resistance is related to the calcium content of the epidermis cells which increase the cell's integrity.…”
Section: Fruit Morphologymentioning
confidence: 99%
See 1 more Smart Citation